Gender Affirmation Surgery: Financial Considerations - Chloe W. Swearingen; Megan Donovan; Jorge Ruiz-Menjivar; Sarah M. Ellis (EDIS)
This 3-page factsheet provides a brief overview of gender-affirming medical care, expenses, and funding options. A glossary with key terms discussed in this publication is included at the end. Written by Chloe W. Swearingen, Megan Donovan, Jorge Ruiz-Menjivar, and Sarah M. Ellis, and published by the UF/IFAS Department of Family, Youth and Community Sciences, November 2020.